After the Fur Trade: The Aboriginal Labouring Class of British Columbia, 1849-1890 - Lutz, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractThis paper challenges the long-standing view that aboriginal people were bystanders in the economic development and industrialization of British Columbia outside, and after, the fur trade. From the establishment of the Colony of Vancouver Island in 1849, through Confederation in 1871 and to the completion of the Canadian Pacific Railway, aboriginal people comprised the majority of the population in present-day British Columbia, and the majority of the workforce in agriculture, fishing, trapping and the burgeoning primary industries.